Serological evidence of MERS-CoV antibodies in dromedary camels (Camelus dromedarius) in Laikipia County, Kenya - Deem, S.L.; Fèvre, Eric M.; Kinnaird, M.; Browne, A.S.; Muloi, Dishon M.; Godeke, G.J.; Koopmans, M.; Reusken, C.B.E.M. (Public Library of Science, 2015)
Middle East respiratory syndrome coronavirus (MERS-CoV) is a recently identified virus causing severe viral respiratory illness in people. Little is known about the reservoir in the Horn of Africa. In Kenya, where no human MERS cases have been reported, our survey of 335 dromedary camels, representing nine herds in Laikipia County, showed a high seroprevalence (46.9%) to MERS-CoV antibodies. Between herd differences were present (14.3%– 82.9%), but was not related to management type or herd isolation. Further research should focus on identifying similarity between MERS-CoV viral isolates in Kenya and clinical isolates from the Middle East and elsewhere.